Design and Synthesis of Novel cyclopeptide Derivatives as New Cytotoxic Agents - Ahmaditaba, Mohammad Ali; Zarghi, Afshin; Houshdar Tehrani, Mohammad Hassan (International Pharmacy Acta, 2018)
A new series of anti-cancer agents based on cyclopeptide scaffold containing methyl sulfonyl group at the para position of the C-4 phenyl ring were synthesized and their cytotoxic activities were determined against several human cancer cell lines. compounds, c Glu-Ser-Pro-Lys-PhSO2Me (1v), c Gly-Pro-Ala-Lys-PhSO2Me (2v) c Ser-Glu-Gly-Pro-Lys-PhSO2Me (3v) c Lys-Gly-Pro-Asp-PhSO2Me (4v) c Asp-Gly-Pro-Lys-PhSO2Me (5v) were synthesized and characterized by lc-mass spectroscopy and NMR .based on the results the most potent cytotoxic cyclicpeptide against A549 cell line was (1v) with IC50 values 3.18 µM and the most potent cytotoxic cyclicpeptide against MCF-7 cell line was (5v) with IC50 values 2.46 µM respectively, while most of the compounds had sufficient activity against MCF-7, HEPG-2 , HT-29 and A-549 cell lines are with mean IC50 values ranging from 2.46 to 31.44 µM. Introduction: The logical design of this study was based on the use of pharmacophoric moiety of COX-2 inhibitors with aromatic or cyclic amino acids and acidic amino acids to simulate the structure of COX-2 inhibitors. As a result, it would be appealing to COX-2 inhibitors with peptide structure which show antitumor and anti-inflammatory effects. Methods and Results: The results clearly indicated that modified cyclopeptides (1v - 5v), showed significant cytotoxic activity against all chosen cell lines. Compound (5v) showed a great anti-cancer activity against MCF-7 cell line and Compound (3v) showed a great anti-cancer activity against A549 cell line. Conclusions: In this study we synthesized 5 modified cyclopeptides by solid phase peptide synthesis approach and examined the cytotoxicity of them on 4 different cell lines. This study indicates that all synthesized compounds showed significant cytotoxicity against different cell lines specially against MCF-7 and A549 cell lines. In addition, modifications on the sequence of modified cyclopeptides had a significant influence on the cell cytotoxicity.